Plankton Communities Behave Chaotically Under Seasonal or Stochastic Temperature Forcings - Guido Occhipinti; Cosimo Solidoro; Roberto Grimaudo; Davide Valenti; Paolo Lazzari (Ecology and Evolution)
ABSTRACT Chaos is observed in natural systems, especially in ecosystems with populations characterized by a short reproductive time scale, such as plankton. We examined if external forcings can be the origin of chaos in a state‐of‐the‐art marine biogeochemical model. Both a seasonal temperature cycle and noise added to this cycle were studied as external forcings, and their interaction with the dynamics resulting from biological interactions, such as competition. Our findings indicate that deterministic periodic forcing can induce chaos in the ecosystem only when biological interactions have already established periodic oscillations within the system. We conclude that random temperature fluctuations can be a driver of chaos in plankton populations, due also to the stochastic nature of the marine environment. The stochastic mechanism for the occurrence of chaos could find wide application in natural systems as it requires no preconditions.